“THE LEGACY OF PROFESSOR SATTAR NAZIMOVICH BABAJANOV IN HYGIENIC SCIENCE OF UZBEKISTAN” - Saloni Sajid Maner (Western European Studies, 2024)
Professor Sattar Nazimovich Babajanov, a distinguished scientist-hygienist, made significant contributions to regional preventive medicine and the development of hygienic science in Uzbekistan. This article explores his life, exemplary work, and scientific achievements, highlighting his role as the founding of the Department of General and Radiation Hygiene, the scientific school of sanitary helminthology and his impact on public health education and training
Keywords: professor; S.N. Babajanov; founder of hygienic science; Uzbekistan; public health